Effect of Light Attenuation through Lithium Disilicate on Polymerization and Microhardness of Dual Cure Resin Cements - Rissanen, Tiina (My University, 2023)
Objectives: This in vitro study aimed to evaluate the effect of ceramic thickness, shade, and light-curing duration and cement type on the degree of conversion and microhardness of dual cured resin cements (DCRC). Methods: Lithium disilicate reinforced glass ceramic (IPS e.max CAD) slabs were fabricated in thicknesses 0.3 mm, 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm and 3.0 mm, and in shades HT A2, LT A2, LT A3 and LT A4. The light attenuation and changes in beam profile were measured through ceramic slabs using a LED light curing unit (Elipar™ DeepCure-S, 3M ESPE) (LCU). Dual cure resin cement specimens (Multilink Automix, Ivoclar Vivadent; Panavia V5, Kuraray; n=3 per subgroup) were light cured through the ceramic slabs for 10 or 40 sec whereas control groups were light cured directly without a ceramic slab or left to cure chemically without light activation in dark. Specimens were dry-stored at 37°C for 24h. Vickers microhardness (VHN) of each specimen were measured on various points, defined using the beam profile obtained through a 3.0 mm LT A2 ceramic slab. Degree of conversion (DC) was measured on the same points using Raman spectroscopy one week after specimen preparation. Differences between groups were analyzed using t-test, one-way ANOVA and Welch’s test. Level of significance was set at 0.05 for statistical analysis. Results: Ceramic thickness and darker shades significantly reduced the light irradiance. Maximum light irradiance measured through ceramic slabs varied at range of 96% for 0.3 mm thick shade HT A2 slab to 5% for 3.0 mm thick shade LT A4 slab. Thickness of the ceramic layer influenced the beam profile, resulting in localized irradiance distribution and showing a more pronounced inhomogeneity with lower irradiance at the periphery of the beam. Differences in light attenuation led to significant differences in VHN and DC of DCRC specimens. Microhardness varied from 35.4 HV (SD 2.6 HV) of Panavia V5 specimens light cured for 10 seconds without a ceramic slab, to 50.6 HV (SD 2.7 HV) of Multilink Automix specimens light cured through a 0.3 mm thick shade LT A4 slab. Degree of conversion varied from 36.3% (SD 2.3%) of Panavia V5 specimens light cured for 40 seconds through a 3.0 mm thick shade LT A4 slab, to 73.1% (SD 4.1%) of Multilink Automix specimens light cured for 40 seconds without a ceramic slab. Conclusions: Restoration thickness and shade, light curing time, and unequal light distribution from the LCU cause variation in light irradiation when luting ceramic restorations with DCRC. The findings of this study emphasize the importance of successful light curing and bring out potential benefits of self-curing DCRC’s in certain clinical situations.
Keywords: Dual cure resin cements, light attenuation, beam profile, microhardness, degree of conversion